Chrysophanol promotes M2 polarization and inhibits M1 polarization through the NF-κB signaling pathway to attenuate sepsis-associated acute kidney injury - Gou, Xuan; Zhang, Wei; Wang, Lele; Tan, Caixia; Wei, Hong; Wang, Xinmin; Zhang, Le (Frontiers in Pharmacology, 2025)
ObjectiveSepsis-associated acute kidney injury (SA-AKI) is a frequent and severe complication in septic patients. This study combines network pharmacology with in vitro and in vivo experiments to preliminarily investigate the protective effect of chrysophanol (CHR) on SA-AKI and its mechanism, aiming to find new therapeutic targets and strategies for SA-AKI treatment.MethodsHK-2 cells were used to investigate CHR’s inhibitory effects on SA-AKI in vitro using CCK-8 assay, Hoechst33258 staining, ELISA, Western blot. In vivo experiments were performed using a septic mouse model, and the therapeutic effect of CHR on SA-AKI and its effect on macrophage polarization were investigated using Hematoxylin and Eosin staining, ELISA, Western blot, and quantitative real-time PCR. Predicting the possible differentially expressed genes and pathways of CHR protecting SA-AKI through network pharmacology. Finally, these pathways were further validated in in vitro experiments by ELISA, Western blot and indirect immunofluorescence staining.ResultsCHR can inhibit LPS-induced injury and apoptosis in HK-2 cells, suppress the expression of inflammatory cytokines TNF-α and IL-6, and enhance its anti-apoptotic and anti-inflammatory effects on HK-2 cells through modulation of macrophages; in in vivo experiments, we obtained the same results that CHR effectively counteracted SA-AKI and played a protective role against mice exerting a protective effect. In addition, based on predictions from network pharmacology and validation from cellular experiments, CHR may exert these effects by inhibiting the NF-κB signalling pathway.ConclusionCHR may protect SA-AKI by inhibiting the NF-κB signalling pathway, promoting M2 macrophage polarisation and inhibiting M1 macrophage polarisation.